(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Fifty-adult male rats were indiscriminately divided into five groups, of similar number: negative control group (group 1), and the groups from 2 to 5 received orally 100 mg/kg b.wt of Pb once a day for 14 days. Then, group 2 was maintained as an untreated positive control group, while the groups 3, 4 and 5 received daily orally Red Dragon Fruit Juice (RDFJ) at a dose of 10, 20 and 30%, respectively. The results exhibited that the fleshy-fruit was higher in its content of phenolics, followed by flavonoids and anthocyanins. As a comparison to untreated positive control group, treated rats with oral administration of RDFJ have a significant (P< 0.05) decrease in serum activity of AST, ALT and ALP enzymes, and the levels of urea nitrogen, uric acid, creatinine and MDA. In addition to the increase in serum activity of catalase (CAT) and GSH-Px enzymes and levels of total antioxidant norepinephrine, dopamine and 5-hydroxytryptamine. Several degradations in cerebral tissue of untreated rats with the brain toxicity were detectable, while an august amendment in the rats treated with the RDFJ, especially with the higher level (30%). Lastly, routine consumption of RDFJ may be profitable to prevent the consequence injury from lead toxicity due to it's a wide range content of flavonids, phenolic and anthocyanins as bioactive compounds.